Metagenomics reveals functional synergy and novel polysaccharide utilization loci in the Castor canadensis fecal microbiome. Issue 11 (November 2018) - Armstrong, Zachary; Mewis, Keith; Liu, Feng; Morgan-Lang, Connor; Scofield, Melanie; Durno, Evan; Chen, Hong; Mehr, Kevin; Withers, Stephen; Hallam, Steven
Abstract The North American beaver (Castor canadensis ) has long been considered an engineering marvel, transforming landscapes and shaping biological diversity through its dam building behavior. While the beaver possesses conspicuous morphological features uniquely adapted for the use of woody plants as construction materials and dietary staples, relatively little is known about the specialized microorganisms inhabiting the beaver gastrointestinal tract and their functional roles in determining host nutrition. Here we use a combination of shotgun metagenomics, functional screening and carbohydrate biochemistry to chart the community structure and metabolic power of the beaver fecal microbiome. We relate this information to the metabolic capacity of other wood feeding and hindgut fermenting organisms and profile the functional repertoire of glycoside hydrolase (GH) families distributed among and between population genome bins. Metagenomic screening revealed novel mechanisms of xylan oligomer degradation involving GH43 enzymes from uncharacterized subfamilies and divergent polysaccharide utilization loci, indicating the potential for synergistic biomass deconstruction. Together, these results open a functional metagenomic window on less conspicuous adaptations enabling the beaver microbiome to efficiently convert woody plants into host nutrition and point toward rational design of enhanced enzyme mixtures for biorefining process streams.